Rancang Bangun Biografi Pahlawan Nasional Berbasis Android - Sam'ani Sam'ani; Muhammad Haris Qamaruzzaman; Sutami Sutami (Department of Science and Technology Ibrahimy University, 2020)
This beloved Indonesian independence is thanks to the great services of the heroes who have valiantly and all their souls fought for the nation from before to after independence. So that the history of the struggle is not forgotten, it is necessary to develop a system that makes it easy for all Indonesian citizens to remember and remember the struggles of the heroes. As the rapid development of technology, especially Android-based smartphones that have been used by almost all walks of life, an application system about the biographical history of the struggle of national heroes can be used anywhere. The problem of this research is how to produce a national hero biography application system based on Android. The software is developed by modeling Waterfall, the system modeling uses UML (Unified Modeling Language). The purpose of this research is to produce a system that will present a biographical history of national heroes visually that can help remember, remember and add to the public's knowledge in getting to know the National Heroes.